A model linking sources of stress to approach and avoidance coping styles of Turkish basketball referees - Anshel, M. H.; Sutarso, T.; Ekmekci, R.; Saraswati, I. W. (Journal of Sports Sciences, 2014)
Purpose of this study was to externally validate and test a conceptual transient model involving six paths that linked sources of acute stress to avoidance and approach coping styles among Turkish basketball referees. The sample consisted of 125 Turkish basketball referees ranging in age from 18 to 36 years (mean = 25.58. s = 3.69). The path analysis tested the relationships simultaneously from stressors, in consecutive order, distractions, subpar performance and verbal abuse, to coping styles, first both avoidance-cognitive and approach-cognitive, and then approach-behaviour. Results indicated that the model achieved a good fit and that all paths tested simultaneously were significant. The distractions stressor was positively related to subpar performance, which, in turn, was positively related to verbal abuse. Verbal abuse was negatively associated with an avoidance-cognitive coping style and positively related to the approach-cognitive coping style. The results also supported a crossover effect of both avoidance-cognitive and approach-cognitive on approach-behaviour. One implication of this study is that coping should be studied in naturally occurring stages, a process-oriented approach. Another implication is that approach and avoidance coping styles, each sub-divided into cognitive and behavioural categories, provide a meaningful framework which provides sports officials a coherent structure for learning and improving ways to cope with acute stress experienced during the contest.